(untitled) (The Review of Diabetic Studies, 2025)
Laboratory tests and nursing care help make sure that every healthcare setting has accurate diagnoses and good treatment. Nurses are very important for getting patients ready, collecting samples correctly, and using test results in real life. It is different from laboratory professionals. This overview looks at how these two areas interact together. From getting a sample to via the information to help patients. It is also important to stress the need for good communication. Also, shared responsibility, and high-quality procedures to lower the risk of mistakes and make patients safer. Healthcare systems may make patient care better, faster, and less likely to go wrong. By improving communication between lab teams and nurses.